Simulation of mixed convection heat transfer in a horizontal channel with an open cavity containing a heated hollow cylinder - Rahman, M.M.; Parvin, S.; Rahim, Nasrudin Abd; Hasanuzzaman, Md.; Saidur, Rahman (Wiley, 2012)
The objective of this paper is to numerically investigate the mixed convective flow and heat transfer controlled by a heated hollow cylinder inside an open cavity attached with a horizontal channel. All the boundaries of the channel and cavity are perfectly insulated while the inner surface of the cylinder is heated uniformly by heat flux q. The equations of conservation of mass, momentum, and energy were solved using adequate boundary conditions by Galarkin's weighted residual finite element technique. The solution has been performed in the computational domain as a whole with proper treatment at the solid/fluid interface. Computations have been conducted for Ra = 10 3-10 5, Prandtl number Pr varying from 0.7 to 7 and ratio of solid to fluid thermal conductivities from 0.2 to 50. Results are presented in terms of streamlines, isotherms, heat transfer rate in terms of the average Nusselt number (Nu av), drag force (D), and maximum bulk temperature (Î¸ max).